Contraception Use among Egyptian Women: Results from Egypt Demographic and Health Survey in 2005 - H Ibrahim Awadalla (JRI, 2012)
Background: The reports of a rise in contraceptive practices have not been matched by a similar decrease in population: therefore, there is a need to look into the causes of this discrepancy. The objectives of this study were to determine the prevalence of different methods of contraception used by Egyptian women, to compare different contraception methods used among various socio-demographic groups and, finally, to identify the main decision makers of contraception use within Egyptian families. Methods: The 2005 Egypt Demographic and Health Survey (EDHS) is a nationally representative household survey of 18134 married women aged 15-49 years. The 2005 EDHS provides a wealth of information on fertility, family planning, maternal and child health and nutrition, and violence against women. The study sample was selected using a multistage sampling technique. A face-to-face structured interview was conducted with each of the selected women. The response rate was 99.5% for completing the questionnaires. Results: The prevalence of contraception was 57.5%, nearly one third of the participants (33.1%) used IUD as a method of contraception. Both male and female were responsible for decision making regarding the use of contraception among different educational levels. Most women reporting use of contraceptive methods were 30-39 years old, were employed, were rich, educated and belonged to urban governorates. Conclusion: More than half of the participants used contraception while IUDs and pills were the most commonly used methods. Whatever the level of education, the majority of women thought that family planning decisions should be made by both partners.
Keywords: Contraceptives, Egypt, Husband, Sociodemographic